Patient with intravascular lymphomatosis: Changes with time in concentrations of serum cytokines - Aoki, Akiko; Ono, Shigeru; Ueda, Atsuhisa; Hagiwara, Eri; Tsuji, Takashi; Ishigatsubo, Yoshiaki (Nihon Rinshō Menʾeki Gakkai kaishi, 2002)
Serum cytokines were evaluated in a patient with intravascular lymphomatosis (IVL). A 62-year-old man was admitted to our hospital for his general malaise, arthralgia, and high-grade fever. He was diagnosed as dermatomyositis, initially. His symptoms were improved by high dose of corticosteroid and immunosuppressive therapy. However his condition deteriorated gradually, and died ten months after the onset of symptoms. Postmortem examination revealed IVL (B cell type). The serum concentrations of inflammatory cytokines, IL-6 and TNF-alpha, were elevated. Level of serum IFN-y was high only at the end of his illness. Serum IL-2 was not detected during the course. Serum IL-4 was slightly elevated. Elevated CRP and hypoalbuminemia might be related to the elevation of these inflammatory cytokines. The clinical diagnosis of IVL is usually difficult because of the absence of specific clinical manifestations and laboratory findings. The time course and/or concentrations of serum cytokines could be a key to make an early diagnosis.